Transmisi dan Motif Pengajian al-Ḥikam Ibn Aṭā’ Allah al-Sakandarī di Pesantren Tambak Beras Jombang - Ali Mas’ud (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2017)
The article seeks to reveal the transmission and motive of Ibn Aṭā’ Allah al-Sakandarī’s al-Ḥikam recitation in Pesantren Tambakberas Jombang under the guidance of KH. Jamaluddin Ahmad. This study employs quantitative and qualitative methods. The qualitative method is used to describe the pattern of transmission of al-Ḥikam, which has been carried out at Pondok Pesantren Tambakberas, while the quantitative one is intended to measure the perceptions of those involved in the recitation of the book in regard to Sufism and political motives that colored the transmission process. Non-parametric inferential statistics are used to measure such perceptions of motives. The recitation of al-Ḥikam constantly transforms the values of Sufism onto the pupils. It can be seen, for instance, within the illustration of such Sufism doctrines as seeking and earning money from lawful occupation, self-restraint from temptations of the world, helping other people, giving charity for the seek of God to face the hereafter life, prohibition of lavish life as it will be the greatest temptation to gain God’s blessing, performing continuous and sincere repentance (tawba naṣūḥa), leaving any unlawfully vague matters (shubhāt), and living independently and abstinence-begging.